If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + 5) = 4n + 10 Reorder the terms: 2(5 + n) = 4n + 10 (5 * 2 + n * 2) = 4n + 10 (10 + 2n) = 4n + 10 Reorder the terms: 10 + 2n = 10 + 4n Add '-10' to each side of the equation. 10 + -10 + 2n = 10 + -10 + 4n Combine like terms: 10 + -10 = 0 0 + 2n = 10 + -10 + 4n 2n = 10 + -10 + 4n Combine like terms: 10 + -10 = 0 2n = 0 + 4n 2n = 4n Solving 2n = 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 2n + -4n = 4n + -4n Combine like terms: 2n + -4n = -2n -2n = 4n + -4n Combine like terms: 4n + -4n = 0 -2n = 0 Divide each side by '-2'. n = 0 Simplifying n = 0
| h^3+1=0 | | 2(5x+1)=10x-3 | | m-14=37 | | 1.9q-4.1-4.2q=3.3q-5.1 | | 8-4(x-2)=8 | | 9(x-7)=-18.9 | | 2x+6y=145 | | 4(a+5)=44.8 | | 5(0)-4y=-20 | | 3=5c-8 | | 40+4x-16=13x-12-3x | | 9e-3=79.8 | | (4v-6)(8+b)=0 | | 10+13+16+4x-8=180 | | 5(a+7)=55 | | -4x^3+25x=24 | | 15+20+25+3x-7=180 | | 11=-3x-7 | | ln(x^2)+ln(16x)-2ln(2x)=3 | | 9+9x=54 | | 16-x=12+2x | | 4x/2+12=2 | | 12-7x=-65 | | -13+4x=-39+10x | | -7+6x=-37 | | x^2-54x-232=0 | | 5x-2+11+11=180 | | 3t^2+5t=-1 | | 5-4y=-20 | | 1=3(4)+b | | 61-2x=5-9x | | 4q+7=-13 |